The microvascular hypothesis underlying neurologic manifestations of long COVID-19 and possible therapeutic strategies. Issue 4 (19th August 2021) - ,
Abstract : With the ongoing distribution of the coronavirus disease (COVID) vaccines, the pandemic of our age is ending, leaving the world to deal with its well-documented aftereffects. Long COVID comprises a variety of symptoms, of which the neurological component prevails. The most permeating theory on the genesis of these symptoms builds upon the development of microvascular dysfunction similar to that seen in numerous vascular diseases such as diabetes. This can occur through the peripheral activation of angiotensin-converting enzyme 2 receptors, or through exacerbations of pro-inflammatory cytokines that can remain in circulation even after the infection diminishes. Several drugs have been identified to act on the neurovascular unit to promote repair, such as gliptins, and others. They also succeeded in improving neurologic outcome in diabetic patients. The repurposing of such drugs for treatment of long COVID-19 can possibly shorten the time to recovery of long COVID-19 syndrome.